DIALOG INTERAKTIF PROGRAM ACARA GELAR WICARA BUDAYA BERLANDASKAN AGAMA HINDU DI PROGRAMA 4 RRI DENPASAR - Sukawinaya, I Wayan; Yuliani, Ni Made; Pramesti Dasih, I Gusti Ayu Ratna (Institut Hindu Dharma Denpasar, 2021)
Radio is classified as a fast and punctual mass media because it uses live broadcasts. Initially including one-way mass media, so that information only goes from source to target without any feedback. The development of radio as a two-way mass media using the telephone. Radio as an interactive medium provides space for listeners' feedback in the concept of interactive dialogue. As is done by Program 4 RRI Denpasar in the Cultural Talk Show program, so that it can be understood the communication patterns applied and their functions and implications. Included in qualitative research, the theories used are; cultural norm theory, S-M-C-R (Source-Massage-Channel-Receiver) theory, and dependency theory of mass communication effects.The findings of the study include: that the communication pattern applied to the interactive dialogue program of the Cultural Talk Show program based on Hinduism in Program 4 RRI Denpasar is a cultural segmentation. The broadcast process using linear and circular communication patterns is divided into three stages, namely the program stage, the technical stage, and the broadcasting stage. Furthermore, there are three functions outlined, namely: an educational function, a socio-cultural function, and a cultural preservation function based on Hinduism. The implications are very real effects on; cognitive strengthening, affective formation, and behavioral development. The concept of interactive dialogue accelerates the feedback process so that feedback is obtained immediately and instantaneously.